Recurrent novae: Type Ia supernovae in the making - Hachisu, I; Kato, M (2001)
We have constructed theoretical light curves for recurrent nova outbursts based on a thermonuclear runaway model. Fitting theoretical light curves with the observations of the eight known recurrent novae provides us with important information about these systems including the mass of the white dwarf, envelope mass at optical maximum, hydrogen content of the white dwarf envelope, and so on. The mass of the white dwarf ranges from 1.35-1.37 M. for seven recurrent novae except for T Pyx which has a less massive white dwarf of 1.2 M.. Further, we have determined net rates of increase for the white dwarf mass as large as similar to(0.1-1.0) x 10(-7) M. yr(-1), and found that the eight known recurrent nova systems will certainly explode as a Type Ia supernova if the donor is massive enough.